Transitional : in one way or another, we all transition - Bergdorf, Munroe (HarperOne, an imprint of HarperCollinsPublishers, 2023)
"Transitioning is an alignment of the invisible and the physical. It is truth rising to the surface. It is one of the most fundamental aspects of the human condition--a part of our experience as a conscious being, no matter who we are. As time goes on, we all develop as people. None of us ever becomes someone else entirely--regardless of how we identify--but nor do we stay the same forever. We all transition. It's what binds us, not what separates us. In Transitional, activist and writer Munroe Bergdorf draws on her own experience and theory from key experts, change-makers and activists to reveal just how deeply ingrained transitioning is in human experience." --